PERANCANGAN SISTEM INFORMASI CONTROL STOCK SPARE PART BEBASIS WEB - Fevi Tri Oktaviani (Program Studi Teknik Informatika Universitas Nusa Putra, 2024)
The spare part stock control recording system is more effective in triggering the company's performance to be better than before. Therefore, we need a system that can handle the process of recording and creating spare part stock control reports using the waterfall model, which is an SDLC method. The hope is that this application can help the performance of the agency. In this thesis the author creates a spare part stock control recording system that will help the administration process at PT. Ichii Industries Indonesia. The spare part stock control system is a system that will record incoming goods, outgoing goods, remaining stock and also prepare spare part stock reports. With this system at PT. Ichii Industries Indonesia can reduce recording errors that may occur. This system can also speed up the process of creating reports which in the end can help PT. Ichii Industries Indonesia.